Hadith #4754 - Sunan Abi Dawud - Abdullah bin Saraqa al-Azdi عبد الله بن سراقة الأزدي; Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Abu 'Ubaidah ibn al-Jarrah; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Al-Bara’ (b. ‘Azib) from the prophet (May peace be upon him) through a different chain of narrators is a similar way.
Grade: Sahih